Resource Allocation for Multi-user Multi-Traffic Class in UWB MANET - Adi Satyanarayana, YV; Padma Raju, K; Naganjaneyulu, PV (International Journal of Computer Sciences and Engineering, 2025)
In this paper we propose to design a Resource allocation for Multi-user Multi-Traffic technique for UWB ad hoc networks as an extension work to MAC protocol for UWB MANET, which combines the DEX Protocol with DU-MAC protocol. Initially the incoming traffic is classified according to their QoS requirements. The packets with strict QoS constraints (like real-time video or voice) are stored in a special queue and other packets are stored in a normal queue. Then resource allocation is done according to packet reception rate (PRR) and queue size. Our work in the paper includes an algorithm for classification of packets, mechanisms for resource allocation for multi-user environment besides estimation of probability of error rate. Our extensive simulations revealed that the proposed approach outperforms existing one in terms of average packet delivery ratio, average end-to-end-delay, packet drop, overhead.